Discovery of bacteriocins from Enterococcus thailandicus HR23 and its role in mediating growth and immune response in rainbow trout (Oncorhynchus mykiss) - Wenhao Ren; Qi Liu; Aihuan Song; Lin Zhong; Xiaolei Shang; Yuxia Wu; Qiang Tu; Yichao Ren (Aquaculture Reports, 2025)
Many probiotics are capable of secreting bacteriocins to inhibit pathogenic microbes. However, the probiotic mechanisms of bacteriocin-producing bacteria in aquatic animals remain poorly understood. This study used inhibition zone assays, electron microscopy and whole-genome sequencing to explore bacteriocins that inhibiting Aeromonas salmonicida from Enterococcus thailandicus HR23 in vitro, and evaluated the role of HR23 on growth and immune response of rainbow trout using feeding experiment in vivo. The results revealed that HR23 produced a peptide-like bactericidal component which was able to disrupt the cell membrane of A. salmonicida. Whole-genome sequencing of HR23 showed that it encoded a variety of genes associated with heat stress, acid and bile salt tolerance. Moreover, HR23 contains manipulators for the synthesis of cyclic bacteriocin, enterocin NKR-5–3B, including the genes enkb, enkb1, enkb2, enkb3, and enkb4. In vivo experiments confirmed that HR23 significantly improved the growth performance of rainbow trout and its resistance to A. salmonicida infection. After supplementing HR23, there were significant changes in intestinal microbiota, with diversity significantly decreased after 14 days and community richness increasing after 21 days. A notable increased abundance of Firmicutes and Bacteroidota while a decreased abundance of Proteobacteria and Verrucomicrobiota were observed at phylum level. In particular, the abundance of beneficial bacteria, such as Bifidobacterium breve, Bacillus, and Lactobacillus increased, while potential harmful bacteria such as Streptococcus, Desulfovibrio, Staphylococcus, Escherichia coli, and Archangium gephyra decreased. The predicted metabolic pathways such as amino acid metabolism and the citric acid cycle in the intestinal microbiota were up-regulated. In addition, supplementation of HR23 was able to activate the immune pathways, such as THαβ and TH1 pathways, while reduced the expression level of inflammation related gene IL-1β. This study provided insights into the mechanisms of bacteriocin-producing bacteria and further explored beneficial microbial bacteriocin metabolites to support healthy aquaculture.